Mekanisme Sewa Menyewa Pohon Kapuk di Kecamatan Bissappu Kabupaten Bantaeng: Tinjauan Fikih Muamalah: Renting Kapok Trees in Bissappu, Bantaeng: A Fiqh Muamalat Review of Ijarah Validity - Sri Ujiana Putri; Saadal Jannah; Karmila (AL-KHIYAR: Jurnal Bidang Muamalah dan Ekonomi Islam, 2026)
This study examines the practice of leasing kapok trees in Bissappu Subdistrict, Bantaeng Regency, and evaluates its conformity with fiqh muamalah (Islamic commercial jurisprudence). It uses a field research design with normative and phenomenological approaches, integrating Islamic legal analysis with real practices in the community. Data were collected through observation, documentation, and in-depth interviews with tree owners and tenants. The findings show that the contract (akad) is conducted orally based on mutual trust, with prices determined through bargaining. Tree owners usually set prices based on estimated harvest yields. However, the lease duration is unclear, as contracts often end when the harvest is completed rather than on a fixed agreed date. After the agreement, owners typically withdraw from management, leaving tenants responsible for all costs and risks, including crop failure and uncertain yields. From a fiqh muamalah perspective, this practice involves significant gharar (uncertainty), especially regarding time and benefits. The object of the contract is also problematic, as it essentially concerns the kapok yield, which is consumable. According to the majority of scholars (jumhur), such a contract is considered an invalid (batil) form of ijarah. This study offers an empirical-legal analysis and recommends alternative contracts, such as profit-sharing partnerships (mudharabah) or service-based ijarah, where the object, duration, and risk mechanisms are clearly defined to ensure fairness and legal certainty.